The biggest treasure of all? ~ the "fifth element" of biodiversity - Evans, Ripley Francis Bruce (Department of Commercial Law, 2023)
The aim of this dissertation is to complete the formal requirements for the University of Cape Town LLM programme (via course work). Whilst drafting the dissertation, the author was mindful of the need for an original academic treatise on the relevant subject matter but a parallel underlying intention was to draft a document that was not only technically correct but also commercially useful. In other words, the intention was to draft a document that a commercial lawyer, advising South African indigenous peoples on the issue of ethno-biological knowledge, could refer to as a 'blue print' for the giving of legal advice to those indigenous peoples or at least a reference point for how to protect and advance their client's rights.